Exploring the impact of YouTube and instructional videos on learning outcomes: A comparative study - Yuliansah Yuliansah; Sutirman Sutirman; Muslikhah Dwihartanti; Maratus Sholikhah (Universitas Negeri Yogyakarta, 2026)
The YouTube platform has become a key learning tool, providing free video content. Meanwhile, with a vast video database and a platform focused on entertainment, many question whether YouTube video content aligns with pedagogical objectives. Therefore, this study aims to compare the learning outcomes of students who use YouTube videos and instructor-developed videos (IDVs) in archival management learning. Using a quantitative approach based on a quasi-non-equivalent control group design with a post-test-only design, this research focuses on test instruments to measure cognitive and psychomotor learning outcomes involving 79 students enrolled in the Records Management course at the Faculty of Vocational Studies, Universitas Negeri Yogyakarta. Data analysis consisted of normality and homogeneity tests. To determine differences between the two groups, the Mann-Whitney U test was conducted in RStudio. The results showed that 1) there was no significant difference in cognitive achievement between students who learned using YouTube videos and instructional videos, and 2) there was a significant difference in psychomotor achievement between students who learned using YouTube videos and instructional videos. This finding indicates that YouTube videos can support students’ cognitive thinking; however, they have not achieved greater skill gains than videos developed with practical learning characteristics. Future studies may identify factors influencing learning outcomes in both groups to examine the extent to which instructional media use supports learning achievement, particularly in the psychomotor domain.